Propuesta para el control de inventarios de la granja avícola Aran S.A.S enfocada en el mejoramiento continuo del proceso. (2024)
The study is aimed at the Aran S.A.S poultry farm, producer and marketer of eggs, located in the village of Cuche, municipality of Santa Rosa de Viterbo, Boyacá. Through diagnosis, deterioration in egg production is detected, a factor that generates economic losses for the company. The problem is even bigger due to the handling of the product once it has been conditioned and placed in the buckets and transferred to the storage warehouse, without adequate order and control regarding the route, since shortcomings had occurred. To address these difficulties, the proposal is made through the Kaizen approach supported by the 5S methodology, Just in Time and Poka Yoke.